Age, dyslexia subtype and comorbidity modulate rapid auditory processing in developmental dyslexia - Lorusso, Maria Luisa; Cantiani, Chiara; Molteni, Massimo (Frontiers in Human Neuroscience, 2014)
The nature of Rapid Auditory Processing (RAP) deficits in dyslexia remains debated, together with the specificity of the problem to certain types of stimuli and/or restricted subgroups of individuals. Following the hypothesis that the heterogeneity of the dyslexic population may have led to contrasting results, the aim of the study was to define the effect of age, dyslexia subtype and comorbidity on the discrimination and reproduction of nonverbal tone sequences. Participants were 46 children aged 8 - 14 (26 with dyslexia, subdivided according to age, presence of a previous language delay, and type of dyslexia). Experimental tasks were a Temporal Order Judgment (TOJ) (manipulating tone length, ISI and sequence length), and a Pattern Discrimination Task. Dyslexic children showed general RAP deficits. Tone length and ISI influenced dyslexic and control children’s performance in a similar way, but dyslexic children were more affected by an increase from 2 to 5 sounds. As to age, older dyslexic children’s difficulty in reproducing sequences of 4 and 5 tones was similar to that of normally reading younger (but not older) children. In the analysis of subgroup profiles, the crucial variable appears to be the advantage, or lack thereof, in processing long vs short sounds. Dyslexic children with a previous language delay obtained the lowest scores in RAP measures, but they performed worse with shorter stimuli, similar to control children, while dyslexic-only children showed no advantage for longer stimuli. As to dyslexia subtype, only surface dyslexics improved their performance with longer stimuli, while phonological dyslexics did not. Differential scores for short vs long tones and for long vs short ISIs predict nonword and word reading, respectively, and the former correlate with phonemic awareness. In conclusion, the relationship between nonverbal RAP, phonemic skills and reading abilities appears to be characterized by complex interactions with subgroup characteristics.